Role of systemic immune-inflammatory index and systemic inflammatory response index in predicting the diagnosis of necrotizing pneumonia in children - Rehab Elmeazawy; Dalia Ayoub; Lamia M. Morad; Ahmed Mohammed Farid EL-Moazen (BMC, 2024)
Abstract Background Necrotizing pneumonia (NP) is a rare serious complication of community-acquired pneumonia (CAP) in children, which is characterized by a protracted course of the disease and a prolonged hospital stay. This study aimed to assess the role of systemic immune-inflammatory index and systemic inflammatory response index in predicting early lung necrotization in children with CAP. Methods This study included all children hospitalized in Pediatric Pulmonology Unit, Tanta University, Egypt, with CAP between the ages of two months and 18 years. Systemic inflammatory indices, including the neutrophil/lymphocyte ratio (NLR), platelet/lymphocyte ratio (PLR), monocyte/lymphocyte ratio (MLR), systemic immune-inflammatory index (SII), and systemic inflammation response index (SIRI), were calculated on patients' admission. Results The study involved a total of 228 children, 42 patients had NP, 46 patients had parapneumonic effusion, and 140 patients had non-complicated CAP. Patients with NP were substantially younger (p = 0.002), stayed in the hospital longer (p < 0.001), had a longer duration of symptoms before hospital admission (p < 0.001), and had fever for a longer duration than those in the other groups (p < 0.001). Regarding the inflammatory ratios, patients with NP had significantly higher MLR, PLR, SII, and SIRI than those in the other groups (p = 0.020, p = 0.007, p = 0.001, p = 0.037, respectively). ROC curve analysis showed that the combined SII + SIRI + D-dimer showed the highest AUC with a good specificity in predicting the diagnosis of NP. Conclusions SII, SIRI, and D-dimer may be beneficial biomarkers for predicting the occurrence of NP in children when performed on patients' admission. In addition, it was found for the first time that combined SII + SIRI + D-dimer had a good sensitivity and specificity in the diagnosis of NP.